Using a look-through simulator to analyze the correlation between functional and optical properties of intraocular lenses - Wu, Zhiyi; Zielińska, Agnieszka; Auffarth, Gerd U.; Rayamajhi, Asu; Britz, Leoni; Khoramnia, Ramin; Łabuz, Grzegorz (Journal of the Optical Society of America. A, Optics, image science, and vision, 2025)
Intraocular lens (IOL) simulators are gaining increasing interest among researchers and clinicians, as they allow users to experience vision through IOLs without the need for implantation. This study examined the correlation between a look-through simulator and the optical properties of modern IOLs, measured using an optical bench. Subjective defocus responses from five observers using a look-through simulator were compared with the through-focus optical quality of IOLs, assessed by measuring the optical transfer function (OTF) and using its components to predict postoperative visual acuity. The analysis of the agreement between OTF metrics and defocus curves confirmed a strong relationship.
Gesehen am 28.10.2025